CACNA1C c.1255G>A Variant Is Associated With an Atypical Timothy Syndrome Phenotype - Victoria Fanucchi, BS; Hemal M. Nayak, MD; Utkarsh Kohli, MD (JACC: Case Reports)
The CACNA1C gene encodes for the Cav1.2 voltage-gated calcium channel. De novo genetic variation in this gene is associated with Timothy syndrome (long QT syndrome type 8) and a wide range of other cardiac phenotypes. This wide phenotypic variability informs the need to study the contribution of CACNA1C genetic variability to phenotypic variability. We report a CACNA1C c.1255G>A(p.Gly419Arg) mutation in a 9-year-old boy and his mother (43-year-old woman) who both presented with an atypical Timothy syndrome phenotype.